2015
DOI: 10.1111/jch.12620
|View full text |Cite
|
Sign up to set email alerts
|

High Blood Pressure in Sub‐Saharan Africa: The Urgent Imperative for Prevention and Control

Abstract: Higher-than-optimal blood pressure (BP), along with tobacco use and dyslipidemia, is one of the three most important modifiable risk factors for CVD. For more than 2 decades, studies have indicated an escalating pattern of hypertension in SSA. 1,2 Estimates indicate unacceptably high rates of undiagnosed and poorly controlled disease in SSA, in spite of substantially enhanced knowledge on pharmacologic and lifestyle interventions for controlling BP. The reasons for the escalating burden of hypertension in SSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
2
20
1
Order By: Relevance
“…This is less than the >50% reported by Awad et al [25]. Almost half of our study participants were physically inactive, a finding which is alarming and higher than the 16.9% reported in West Cameroon [17], and almost twice as high as previous estimates for SSA [5]. Over one in five participants reported alcohol use.…”
Section: Discussioncontrasting
confidence: 81%
“…This is less than the >50% reported by Awad et al [25]. Almost half of our study participants were physically inactive, a finding which is alarming and higher than the 16.9% reported in West Cameroon [17], and almost twice as high as previous estimates for SSA [5]. Over one in five participants reported alcohol use.…”
Section: Discussioncontrasting
confidence: 81%
“…This changing circumstance is of great concern in SSA, given the dual burden of communicable and non-communicable diseases (NCDs) with which many resource-constrained countries in the region must now contend [ 2 , 4 7 ]. The situation is aggravated by the increased risk of adverse outcomes, primarily due to lower levels of hypertension awareness and control, a younger age of onset of the disease, and a potentially more aggressive disease course observed in persons of black African ancestry [ 1 , 2 , 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, currently available literature consistently underlines the need for more nationally representative surveys to better elucidate the country-level burden of hypertension and the problem it presents for the SSA region [ 3 , 4 , 8 10 , 12 ]. This need for national-level data on hypertension burden appears particularly relevant given reports that the prevalence of hypertension in some SSA countries is among the world’s highest [ 8 , 11 , 13 ]. Indeed, a 2012 cross-sectional study of hypertension across four rural and urban communities in SSA reported age-standardized prevalence estimates of 19.3% (95%CI:17.3–21.3), 21.4% (19.8–23.0), 23.7% (21.3–26.2) and 38.0% (35.9–40.1) in rural Nigeria, rural Kenya, urban Tanzania and urban Namibia, respectively [ 15 ], supporting theories of the magnitude of the hypertension burden in SSA and providing shocking evidence of a remarkably high burden among urban Namibian residents (crude: 32.0%; age-standardized: 38.0%) similar to that of non-Hispanic black adults in the USA (38.6%) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1] The prevalence of hypertension in Nigeria has been recorded to be 20% and in Bayelsa State, it has been estimated to be as high as 27.8% and several risk factors and morbidities identified. [2] Consultations, investigations, pharmacotherapy, lifestyle modification practices and in patient care are known to contribute to the cost of care of people living with hypertension.…”
Section: Introductionmentioning
confidence: 99%